Pengaruh Penggunaan Model Pembelajaran Problem Based Learning Berbantuan Fishbone Dalam Meningkatkan Keterampilan Proses Sains Siswa - Kurniati; Sri Wahyuni; Sitti Asmah (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2025)
This study aims to understand the influence of Problem-Based Learning model assisted by Fishbone in developing science process skills on learning outcomes of 10th-grade students at SMA Negeri 12 Bone. The population of the research was all 10th-grade students at SMA Negeri 12 Bone, with the research sample selecting one class, specifically all students in class X6 totaling 35 students. Data collection techniques involved distributing questionnaires and documentation. The research type was a pre-experimental design using the "One-shot Case Study" research design. Data analysis techniques employed descriptive statistical analysis and inferential statistical analysis by conducting normality tests, homogeneity tests, and hypothesis testing using SPSS version 23. Research results showed that the use of Problem-Based Learning model assisted by fishbone has a significant influence on science process skills of 10th-grade MIPA 6 students at SMA Negeri 12 Bone.